1998
DOI: 10.1097/00005768-199811000-00002
|View full text |Cite
|
Sign up to set email alerts
|

A prospective controlled study of diagnostic imaging for acute shin splints

Abstract: MRI may be used rather than TPBS and radiographs for evaluating acute tibial pain in athletes where avoidance of radiation exposure is desirable. Similar sensitivity and specificity may be expected from both investigations; however, in the light of abnormal TPBS and MRI findings in control and asymptomatic limbs, we recommend further studies be performed to define the extent of nonpathological TPBS and MRI changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
76
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 30 publications
2
76
3
Order By: Relevance
“…In the present study we asked athletes to report his- The most common presentation of ERLP was bilateral medial leg pain, in agreement with the findings of previous studies. 3,39,40 This symptom presentation is most consistent with medial tibial stress syndrome, a common pathoanatomic presentation of ERLP. 4,5,53 The second most common presentation was lateral leg pain, which is most consistent with the location of anterior or lateral chronic exertional compartment syndrome symptoms.…”
Section: Discussionmentioning
confidence: 55%
“…In the present study we asked athletes to report his- The most common presentation of ERLP was bilateral medial leg pain, in agreement with the findings of previous studies. 3,39,40 This symptom presentation is most consistent with medial tibial stress syndrome, a common pathoanatomic presentation of ERLP. 4,5,53 The second most common presentation was lateral leg pain, which is most consistent with the location of anterior or lateral chronic exertional compartment syndrome symptoms.…”
Section: Discussionmentioning
confidence: 55%
“…Anecdotally, the authors believe this test provides greater sensitivity and specificity than the other aforementioned tests when assessing for tibial stress fracture. Although the percussion test, percussing the heel with the examiner's palm, has been reported 1,15,21 as useful in the diagnosis of lower extremity stress fractures, no studies have reported on the sensitivity, specificity, or likelihood ratios of this test. Localized point tenderness over an area no larger than 5 cm has been recommended as a differentiating test in comparison to a larger region of tenderness, which would be suggestive of shin splints.…”
Section: Discussionmentioning
confidence: 99%
“…Localized point tenderness over an area no larger than 5 cm has been recommended as a differentiating test in comparison to a larger region of tenderness, which would be suggestive of shin splints. 1 Due to the lack of a proven clinical test for diagnosing tibial stress fractures, clinicians should rely upon a thorough patient history, palpatory examination, ancillary testing, and serial examinations in a patient who fails to respond to early management.…”
Section: Discussionmentioning
confidence: 99%
“…Radiograph is unreliable in early diagnosis where MR imaging is better modality as it detects early changes of osseous stress injury. Bone scan is extremely sensitive but suffer from false positive rates of up to 11-23% [5,6]. All our cases were subjected to plain radiograph of affected and opposite limb and findings suggestive of stress fracture was seen in 23 cases (39%).…”
Section: Discussionmentioning
confidence: 97%